2013
DOI: 10.1177/0009922813500339
|View full text |Cite
|
Sign up to set email alerts
|

Does Trainee Involvement Affect Anticipatory Guidance in Well-Child Care?

Abstract: Priority anticipatory guidance is covered only one third as often when the well-child visit is not conducted by the primary attending. When involving trainees, continuity of care and parental concerns must be emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Furthermore, using email or mobile messaging apps may further reduce costs and possibly increase the spread of the intervention [49]; even if equity is a challange for technology-based parenting interventions [54,55]. The Baby Newsletter allows all parents to receive written pediatric anticipatory guidance that would otherwise not be received and extends the pediatrician's contact with the family [25,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using email or mobile messaging apps may further reduce costs and possibly increase the spread of the intervention [49]; even if equity is a challange for technology-based parenting interventions [54,55]. The Baby Newsletter allows all parents to receive written pediatric anticipatory guidance that would otherwise not be received and extends the pediatrician's contact with the family [25,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers with different ethnic/racial background can all benefit from pediatric AG directly and/or indirectly to reduce stress and promote effective parenting practices. Given that pediatric providers have identified many barriers to AG provision, including lack of time, training, reimbursement, and potential resources for referral (Erickson, Hill, & Siegel, 2001; Sgrignoli, Lehman, & Sekhar, 2014), how to balance the expanding recommendations for AG and efficiency of AG delivery (Coker, Windon, Moreno, Schuster, & Chung, 2013) will be an important topic for future research. In addition to investigating direct effects, explicating the mediating mechanism allowed us better to understand the role of parental stress in linking AG to parenting.…”
Section: Discussionmentioning
confidence: 99%
“…In New York City, a 2007 modification to regulations on beverage offerings in childcare facilities stated SSBs should not be provided, and a follow-up study indicated that 67% of centers were in compliance. 21,22 Providers inquiring about daily SSB intake should remind parents to include SSBs offered in their childcare center in the "total." However, policy alone is unlikely to be successful in reducing SSB intake among young children.…”
Section: Discussionmentioning
confidence: 99%
“…This counseling frequently involves recommendations on nutrition, diet, and exercise. 21,22 Providers inquiring about daily SSB intake should remind parents to include SSBs offered in their childcare center in the “total.” Parents should be made aware that if their child is enrolled in outside of home care, SSBs may be routinely offered with snacks or meals. Providers can explain to parents that this information may not be provided as part of a daily report on meals and toileting.…”
Section: Discussionmentioning
confidence: 99%